Absolute determination of the X‐ray absorption coefficient of barium in the L region using a liquid absorption cell. (22nd November 2012) - Kodre, Alojz; Padežnik Gomilšek, Jana; Hauko, Robert; Šala, Martin; Arčon, Iztok
<x xml:space="preserve">Abstract</x> A method of absolute measurement of X‐ray absorption coefficient is proposed, on the basis of the use of an adjustable pathlength liquid cell and a solution of the investigated element. A variational analysis of the measured data is developed to remove some sources of systematic error. A check of the exponential attenuation with thickness is used to suppress beam harmonics admixture and dark current drifts. The method is illustrated by a measurement on Ba in the L edge region, using aqueous solution of Ba nitrate. Measured data provide information on detailed energy dependence of the absorption beyond the Victoreen‐like trends reproduced in compilations. The proposed method provides a way to measure the absorption data for practically all elements and a wide range of photon energies. Copyright © 2012 John Wiley & Sons, Ltd.